A formação de professores/as de arte em educação para as relações étnico-raciais : interrogando os currículos de licenciatura em teatro - Reis, Monique Priscila de Abreu (2017)
The research which resulted in this dissertation aimed to understand the manner the University is incorporating the racial-ethnic theme on the curriculums of the Arts degree course, specifically in two Theater degree courses, one from Universidade Federal de Minas Gerais and the other one from Universidade Estadual Paulista. This research fall within the wide-ranging debate which has as reference the Law 10.639/2003, attempting to understand how the future teachers of arts are being trained in the racial-ethnic relations and the teaching of Afro-Brazilian History and Culture. The methodology applied was the Grounded Theory and consisted of document and bibliographic research and interviewing researchers of the field and students who were about to finish their course. After the data analysis, important contribution was gathered to think of actions to (re)test and (re)plan the basic training of Theater teachers in such theme, searching for new contents and pedagogical-didactics that come from an ethnocentric education, mainly from a European aspect, and bring a more plural education on which the differences are appreciated, as well as different ways of conceiving and performing theater are contemplated. To that extent, the barrier-breaking between the university and the community shows up, on the data, as a central issue to new perspectives of training teachers.